2020
DOI: 10.1111/dth.13922
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidity, depression, and anxiety levels and quality of life of the patients with mycosis fungoides

Abstract: Mycosis fungoides (MF) is a chronic disease, causing serious morbidities and mortality. This study was designed to measure depression and anxiety levels in MF patients, and quality of life (QoL) assessments and to compare the results with controls. Fifty-two patients with a diagnosis of MF and 52 age and sex matching healthy controls were enrolled in this study. Beck Depression Inventory (BDI), Beck Anxiety Inventory (BAI) and the 36-Item Short Form Health Survey (SF-36) were administered to all patients and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 34 publications
1
25
0
Order By: Relevance
“…In the 24 included studies in this review, QoL was reported for heterogeneous study populations with various stages of the disease and differences in prior‐ and current therapies 5,6,11–32 . The vast majority of studies described study populations that featured stage MF IA‐IVB and SS and did not report separate results for early and late‐stage disease (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the 24 included studies in this review, QoL was reported for heterogeneous study populations with various stages of the disease and differences in prior‐ and current therapies 5,6,11–32 . The vast majority of studies described study populations that featured stage MF IA‐IVB and SS and did not report separate results for early and late‐stage disease (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 24 studies matched the eligibility criteria. 5,6, All included studies were published between 2001 and 2020.…”
Section: Methodological Resultsmentioning
confidence: 99%
See 3 more Smart Citations